EFISIENSI DAN IDENTIFIKASI LOSS PADA PROSES PENGOLAHAN TERASI UDANG REBON (Acetes sp) DI DESA BELO LAUT KECAMATAN MUNTOK BANGKA BELITUNG - Erta Afriza Andriyani; Kiki Yuliati; Agus Supriadi (Jurnal FishtecH, 2012)
The objective of this research was to study the efficiency and identification on each processing of terasi shrimp and recommendation to repaired. The research was conducted from August 2009 until July 2012 in Belo Laut village, Bangka Belitung Province. The objective of this research was to study the efficiency, to identify losses during the processing of terasi and to formulate recommendations for process improvement. Laboratory analysis was conducted in Bioprocess Laboratory at Chemical Enginering, Enginering Faculty, Sriwijaya University. Parameters observed were the contents of water, ash, protein, fat, and carbohydrate.. The data were analysed descriptively. The results showed that the efficiency was 35.73%. Based on Pareto diagram, the improvement priority which need to be done is for the dominant loss of shrimp that is wasted on the salinity (36.76%), left on the machine (26.47%), and wasted on drying I (16.18%). The cause-effect diagram analysis shows that the causing factor of the dominant loss come from equipment and human/worker factors. The results of laboratory on nutrient composition terasi showed that average water content (wb) was 35.21%, protein content (db) was 37.88%, fat content (db) was 1.85%, ash content (db) was 9.35%, and carbohydrate content (db) was 50.94%.